2021
DOI: 10.1080/23802359.2021.1981165
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Turdus obscurus (Passeriformes: Turdidae)

Abstract: The Eyebrowed Thrush ( Turdus obscurus ) is a highly migratory bird, which breeds in northeastern Asia and overwinters in southeastern Asia. We obtained the mitochondrial genome of T. obscurus by Sanger sequencing. The mitogenome was 16,739 bp in length, which contains 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. Its composition is consistent with the species in genus Turdus . Phylogenetic analysis based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Muscicapidae and Turdidae were sister groups (BP = 85, BPP = 1.00), and they clustered together with Sturnidae (BP = 100, BPP = 1.00), Our results showed that Muscicapidae, Turdidae, and Paradoxornithidae were clustered into two monophyletic groups, and species of the same genus were clustered together with a high degree of confidence. Muscicapidae and Turdidae were sister groups (BP = 85, BPP = 1.00), and they clustered together with Sturnidae (BP = 100, BPP = 1.00), which was consistent with a previous study [38]. T. indicus and T. cyanurus were clustered together with high confidence (BP = 100, BPP = 1.00).…”
Section: Mitochondrial Phylogenomicssupporting
confidence: 89%
“…Muscicapidae and Turdidae were sister groups (BP = 85, BPP = 1.00), and they clustered together with Sturnidae (BP = 100, BPP = 1.00), Our results showed that Muscicapidae, Turdidae, and Paradoxornithidae were clustered into two monophyletic groups, and species of the same genus were clustered together with a high degree of confidence. Muscicapidae and Turdidae were sister groups (BP = 85, BPP = 1.00), and they clustered together with Sturnidae (BP = 100, BPP = 1.00), which was consistent with a previous study [38]. T. indicus and T. cyanurus were clustered together with high confidence (BP = 100, BPP = 1.00).…”
Section: Mitochondrial Phylogenomicssupporting
confidence: 89%
“… 2020 ), Phoenicurus phoenicurus MN122900 (unpublished) and Turdus obscurus MZ337397 (Zhang et al. 2021 ). We used Cnemotriccus fuscatus AY596278 (Slack et al.…”
Section: Methodsmentioning
confidence: 99%